2014
DOI: 10.4172/2325-9639.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness, Circadian Preference, Caffeine Consumption and Khat Use among College Students in Ethiopia

Abstract: Objectives To estimate the prevalence of daytime sleepiness and circadian preferences, and to examine the extent to which caffeine consumption and Khat (a herbal stimulant) use are associated with daytime sleepiness and evening chronotype among Ethiopian college students. Methods A cross-sectional study was conducted among 2,410 college students. A self-administered questionnaire was used to collect information about sleep, behavioral risk factors such as caffeinated beverages, tobacco, alcohol, and Khat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…The prevalence of EDS in this study is similar to other studies from Southern University of United States (31% vs 27%) [39], Universidad San Martin de Porres in Lima, Peru (31% vs 35%) [40], Nigeria (31% vs 32.5%) [41], Southern Taiwan (31% vs 35%) [42], and Ethiopia (31% vs 26%) [17]. High magnitude of EDS in students could be explained by the highly competitive and demanding learning environment that disrupts the regular sleep time [12].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of EDS in this study is similar to other studies from Southern University of United States (31% vs 27%) [39], Universidad San Martin de Porres in Lima, Peru (31% vs 35%) [40], Nigeria (31% vs 32.5%) [41], Southern Taiwan (31% vs 35%) [42], and Ethiopia (31% vs 26%) [17]. High magnitude of EDS in students could be explained by the highly competitive and demanding learning environment that disrupts the regular sleep time [12].…”
Section: Discussionsupporting
confidence: 87%
“…The role of cortisol on the development of depression could be explained by the neurotoxic effect of cortisol on hippocampus [56]. Other studies reported the association of EDS to stress [45,57], Khat chewing, alcohol consumption and cigarette smoking [17], female sex [20,22] and male sex [21]. However, these factors were not predictors of EDS in our study which might be due to variations in sample size and sociocultural factors.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Evening chronotypes were reported to consume more alcohol and caffeine, which is widely recognised for its stimulant properties that can boost wakefulness and concentration by increasing brain activity [83][84][85]. However, many other studies have demonstrated how an excessive intake of alcohol and caffeine can result in reduced sleep duration and quality, increased fatigue and daytime sleepiness, and delayed sleep onset [85][86][87][88][89][90]. According to Galli et al (2013), each alcoholic drink (contain 14g of alcohol) can reduce sleep duration by 30 min.…”
Section: Macro and Micro Nutrients And Food Groupmentioning
confidence: 99%
“…The mechanism underlying this association is still unclear, but it is proposed that both alcohol and caffeine intakes can delay the onset on nocturnal melatonin release, thus suppressing sleepiness [83,91]. Interestingly, some studies revealed how the consumption of alcohol and caffeine can increase the odds of later chronotype [90,92]. It was postulated that evening chronotypes have more chances to engage with 'evening habits' (drinking) due to a delay in sleep time compared to morning chronotypes, who sleep earlier [93].…”
Section: Macro and Micro Nutrients And Food Groupmentioning
confidence: 99%